BUSINESS CHANGES, INJURY RISKS AND WORK ILLNESSES (Fiep Bulletin - online, 2014)
The study aims to examine the impact of business changes on the risks of accidents and the prospects for preventive actions from physical education. The population consisted of 2830 workers, attended by the Reference Center on Health Workers in Greater Recife / PE, between the years 2008-2012. Data were analyzed using techniques of descriptive and inferential statistics, through the Statistical Package for Social Sciences software version 17. The margin of error was 5.0 % and ranges with 95.0 % reliability. And work-related accidents ; biological, chemical, physical and psychological , were studied. The results showed that the ergonomic and psychological factors contribute to the occurrence of accidents when companies are undergoing intense changes. Pointing to demand performance of the physical educator, in a multidisciplinary team , in the prevention of accidents and risks of illnesses.
Keywords: Changes; Risks of accidents; Physical Education.